Vascular endothelium and inflammatory process, in patients with combined Type 2 diabetes mellitus and coronary atherosclerosis: the effects of vitamin C. - Antoniades, C; Tousoulis, D; Tountas, C; Tentolouris, C; Toutouza, M; Vasiliadou, C; Tsioufis, C; Toutouzas, P; Stefanadis, C (2004)
AIMS: Type 2 diabetes mellitus (DM) and coronary artery disease (CAD) are both associated with endothelial dysfunction and elevated oxidative and inflammatory state. We examined the effect of vitamin C on endothelial function and levels of soluble vascular cell adhesion molecule (sVCAM-1), interleukin-6 (IL-6) and tumour necrosis factor (TNF-alpha), in DM patients with or without CAD and in non-diabetic subjects. METHODS: Thirty-seven patients with DM + CAD, 17 patients with DM without CAD and 21 non-diabetic subjects were divided into groups receiving vitamin C 2 g/day or no anti-oxidant for 4 weeks. Forearm blood flow was determined using venous occlusion gauge-strain plethysmography. Forearm vasodilatory response to reactive hyperemia was considered as index of endothelium-dependent dilation. RESULTS: Baseline levels of IL-6 and TNF-alpha were significantly higher in patients with DM + CAD compared with patients with DM (P < 0.01) or non-diabetic subjects (P < 0.01). IL-6 and TNF-alpha levels were also higher in DM compared with non-diabetic subjects (P < 0.05). sVCAM-1 levels were lower in non-diabetic controls compared with DM + CAD (P < 0.05) or DM (P < 0.05). Reactive hyperaemia was higher in non-diabetic controls compared with DM + CAD (P < 0.001) or DM (P < 0.001). Vitamin C significantly increased reactive hyperaemia only in the DM + CAD group, while it had no effect on serum levels of sVCAM-1, TNF-alpha and IL-6 in any of the groups. CONCLUSIONS: Type 2 diabetes mellitus is associated with impaired endothelial function and increased levels of TNF-alpha, IL-6 and sVCAM-1, especially in patients with DM and CAD. Vitamin C significantly increased forearm vasodilatory response to reactive hyperaemia only in patients with combined DM and CAD.